Development of Software for Dielectric Analysis - Lim, Long Hsiang (2002)
A software was developed using Visual Basic 6.0 for the study and analyzing of the experimental data for the dielectric laboratory. For this purpose, a numerical computation of Kramers-Kronig relations, fitting various dielectric functions and plotting dielectric graphical representations were created and was found to achieve high level of accuracy when compared with the simple non-interacting Debye model. The software was used to analyze the experimental data of rose extract diluted in water. The experimental data of rose extract diluted in water shows that the polarisation consists of two different mechanisms, represented by a characteristic loss peak and a strong low frequency dispersion. The mechanisms were in consistent with the Kramers-Kronig relations and equivalent circuits were proposed for the material under study.